Flood risk management in Japan in response to climate change: shift from river channel-focused control to watershed-oriented management - Juan Fan; Guangwei Huang (Emergency Management Science and Technology, 2023)
Flood risk increase due to climate change is one of the world's most pressing issues. Different countries and regions may take or have taken different approaches to deal with it. Therefore, information sharing and learning from each other are essential for achieving flood risk reduction on a global scale, especially in times of climate change. This paper provides a diagnosis of challenges in flood risk management in Japan in response to climate change. It highlights change in hazard and exposure and increase in vulnerability. Further, it placed its attention on new strategies taken by the Japanese government to counteract climate change impacts with a particular focus on the latest legal development to better support flood risk management. Although there are large amounts of research concerning climate action in the existing literature, the majority of them focus on technical and social aspects. The present study enriches literature on flood risk management and sheds new light on how to advance integrated river basin management.